2017
DOI: 10.1038/s41598-017-15414-5
|View full text |Cite
|
Sign up to set email alerts
|

Neural-specific deletion of mitochondrial p32/C1qbp leads to leukoencephalopathy due to undifferentiated oligodendrocyte and axon degeneration

Abstract: Mitochondrial dysfunction is a critical step in the pathogenesis of many neurodegenerative diseases. The p32/ C1qbp gene functions as an essential RNA and protein chaperone in mitochondrial translation, and is indispensable for embryonic development. However, little is known about the consequences of mitochondrial dysfunction of p32 deletion in the brain development. Here, we found that mice lacking p32 in the central nervous system (p32cKO mice) showed white matter degeneration accompanied by progressive olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Previously, we observed that knockout of the mitochondrial protein, p32/C1qbp, in mice caused the dysfunction of mitochondrial translation and ER stress induction, leading to induction of ISR genes [5,6]. As shown in Figure 2, eIF2α phosphorylation at Ser 51 , a well-established indicator of ER stress, was increased 2-4 h after CAP treatment MEF cells.…”
Section: Cap Induces the Er Stress Responsementioning
confidence: 67%
See 3 more Smart Citations
“…Previously, we observed that knockout of the mitochondrial protein, p32/C1qbp, in mice caused the dysfunction of mitochondrial translation and ER stress induction, leading to induction of ISR genes [5,6]. As shown in Figure 2, eIF2α phosphorylation at Ser 51 , a well-established indicator of ER stress, was increased 2-4 h after CAP treatment MEF cells.…”
Section: Cap Induces the Er Stress Responsementioning
confidence: 67%
“…The reverse transcription (RT) product was then subjected to real-time PCR analysis with SYBR Premix ExTaq™ II and the StepOnePlus Real-Time PCR System (Applied Biosystems, Carlsbad, CA, U.S.A.). Total mRNA from wild type and homozygous p32loxP/loxP mice (nestin-Cre +/− , p32loxP/loxP) were previously described [6]. Mouse experiments and protocols were performed in accordance with the guidelines of the animal ethics committee of Kyushu University Graduate School of Medicine, Japan (#A29-052-0).…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…One top-scoring YBEY partner was the putative RNA-binding protein p32/C1QBP, critically required for mitochondrial metabolism and associated with a variety of mitochondrial diseases and cancer (67)(68)(69)(70)(71)(72)(73)(74)(75)(76). The interaction between the two proteins was confirmed in cross-pulldown assays with the alternate use of YBEY-3×FLAG and p32-HA proteins as bait and prey (Supplementary Figure 8A).…”
Section: Ybey Interacts With P32 and A Distinct Set Of Mitoribosomal mentioning
confidence: 86%